Strategies for Promoting Education in Student Recruitment in Pesantren - Sormin, Darliana; Rahmayanti, Mira; Hasanah, Dani (Pascasarjana Universitas KH. Abdul Chalim, 2025)
This study was conducted at Pondok Pesantren Darul Mursyidi Sialogo, Angkola Barat District, South Tapanuli Regency, using a qualitative approach. The research aims to obtain descriptive data through observation, interviews, and documentation. Primary data were collected directly from the school principal and teachers, while secondary data came from various written sources. The data analysis was carried out in three stages: data reduction, data presentation, and conclusion drawing. The findings reveal that the pesantren's promotion strategies for recruiting new students include school outreach, the use of brochures and banners, collaboration with community leaders, and the use of social media. Recruitment efforts are also supported by religious lectures and Friday sermons. Furthermore, the roles of teachers, students, and parents are essential in promoting student admissions. The implemented recruitment strategies are divided into three stages: (1) promotion through print and digital media, (2) student selection based on religious aptitude, and (3) socialization to help new students adapt to the pesantren environment. These strategies have proven effective, as evidenced by the increasing number of new students each year. The study concludes that the success of student recruitment at Pondok Pesantren Darul Mursyidi Sialogo is closely linked to the synergy between the pesantren, educators, students, parents, and community leaders. This collaboration contributes to building a positive image of the pesantren as a high-quality Islamic educational institution.